Business Development of “Amma” Brand Medical Devices - Annisa Nur Utami Paulain; Keni Kaniawati (Publikasi Indonesia, 2024)
Good distribution of medical equipment is an important element in an efficientlyfunctioning health system. Nowadays this business is growing up very fast as shown innumbers of registered distributors which increases in just several years. PT.AMMA SadayaIndonesia is one of company which holding legal and permission to importing and distributingmedical equipment in Indonesia since 2021. Seeing this condition the company strives todevelop its business in order to expand the market and improve product quality and sales.This business plan aims to conduct a feasibility study and analyze aspects related to businessdevelopment. With qualitative research methods in this business plan we analyze all theseaspects. The research results show that in terms of business planning, environmental analysis,marketing aspects, operations aspects, human resources aspects, financial aspects, it appearsthat the AMMA company's business is worthy of development. Especially from the financialaspect, it can be seen that the results of the analysis of the R/C ratio, payback period, NPV andIRR are in the business category that is worth developing. Meanwhile, from the Timmonsmodel analysis, design thinking, SWOT analysis and canvas business model, it can be seen howthis business should be developed. SWOT analysis shows that an aggressive developmentstrategy is the best strategy for AMMA company development.